2019
DOI: 10.3329/birdem.v9i3.43080
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic activity of ethanolic extract of Caulerpa recemosa

Abstract: Background: Caulerpa recemosa, also known as sea grape, is a stout straggling prostrate shrubby plant with spinous stipules and uniaxial siphonous thallus, mostly divided into a creeping axis (stolon), with rhizoids and erect shoots (fronds), either nude, leaf-like or with grape or feather-like ramuli. Caulerpa racemosa has erect fronds up to 9-13 cm high bearing un-crowded vesiculate ramuli that are radially arranged. Fronds are slightly inflated above the attachment to the stolon which are fixed to the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
0
1
2
Order By: Relevance
“…Rajasekar et al [33] reported that betacyanin was found to be present in green seaweeds. Other studies [34,35,36] found that C. racemosa possess alkaloids, flavonoids, glycosides, phenols, saponins and steroids, however, these secondary metabolites were not detected qualitatively in the ethanolic extract of our samples. The differences in results could be attributed to some factors like climatic condition, season, species, subspecies, harvest and the method used for extraction of compounds which greatly affects the chemical compositions of the extract [37].…”
Section: Table 2 Phytochemical Constituents Of Seaweed Ethanolic Extr...contrasting
confidence: 74%
“…Rajasekar et al [33] reported that betacyanin was found to be present in green seaweeds. Other studies [34,35,36] found that C. racemosa possess alkaloids, flavonoids, glycosides, phenols, saponins and steroids, however, these secondary metabolites were not detected qualitatively in the ethanolic extract of our samples. The differences in results could be attributed to some factors like climatic condition, season, species, subspecies, harvest and the method used for extraction of compounds which greatly affects the chemical compositions of the extract [37].…”
Section: Table 2 Phytochemical Constituents Of Seaweed Ethanolic Extr...contrasting
confidence: 74%
“…Sharma et al [40] found that the ethanolic extract of C. okamurae was effective in preventing body weight gain and fat accumulation and reduced plasma and hepatic lipid profiles. Likewise, Rahman et al [41] reported that the ethanolic extract of C. recemosa could potentially be used as a hypolipemic agent since it exhibited a significant hypolipemic effect at a dose of 200 mg/kg body weight. Based on this information, lipid extracts from Caulerpa have the potential as a food supplement or agent for good health that might be beneficial for aging societies and people with diabetes or hyperlipidemia.…”
Section: Antioxidant Properties and Applicationsmentioning
confidence: 99%
“…Menurut Gambar 1 Lokasi pengambilan sampel rumput laut Iveša et al (2004), C. taxifolia memiliki proporsi asam lemak jenuh berkisar antara 45,2-73,7%, asam lemak tak jenuh tunggal 10,3-25,9% dan tak jenuh ganda sebesar 16-34,3%. Caulerpa racemosa memiliki kandungan seperti terpenoid, asam lemak poliasetilenik, saponin, steroid, alkaloid, tanin, tirosin, glikosida, kumarin, phlobatannin, karbohidrat, flavonoid dan protein, serta caulerpin (Nurjanah et al, 2016;Kumar et al, 2019;Rahman et al, 2019;Subramanian et al, 2019).…”
Section: Pendahuluanunclassified
“…Rumput laut C. taxifolia dan C. racemosa memiliki aktifitas farmakologis antiproliferatif, antivirus, antikoagulan, antioksidan, antiradang, antimikroba, antijamur, antikanker dan antirematik (Sumanya et al, 2015;Ramakrishnan et al, 2015;Ferramosca et al, 2016;Rahman et al, 2019). Hasil penelitian Nagappan & Vairappan (2014) menunjukkan bahwa C. racemosa mengandung senyawa fenol sebagai komponen non gizi.…”
Section: Pendahuluanunclassified